2019
DOI: 10.1007/s00421-019-04218-2
|View full text |Cite
|
Sign up to set email alerts
|

The time course of adaptations in thermoneutral maximal oxygen consumption following heat acclimation

Abstract: Purpose This study investigated the effects of a 10-day heat acclimation (HA) programme on the time course of changes in thermoneutral maximal oxygen uptake ($$\dot{V}$$ V ˙ O2max) during and up to 10 days post-HA. Methods Twenty-two male cyclists were assigned to a HA or control (Con) training group following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 48 publications
1
26
1
Order By: Relevance
“…Our data agree with a recently published meta-analysis with 23 studies which reported a small but significant effect of HA onV O 2 max (Hedge's g = 0.30) measured in a temperate environment (Benjamin et al, 2019 or approximately 5%) in a temperate environment using trained cyclists . Recently, Waldron et al (2019) Figure 1). We propose that these results may be due to a higher absolute intensity (walking/running speed) and heat accumulation experienced by our participants with greater baselineV O 2 max .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data agree with a recently published meta-analysis with 23 studies which reported a small but significant effect of HA onV O 2 max (Hedge's g = 0.30) measured in a temperate environment (Benjamin et al, 2019 or approximately 5%) in a temperate environment using trained cyclists . Recently, Waldron et al (2019) Figure 1). We propose that these results may be due to a higher absolute intensity (walking/running speed) and heat accumulation experienced by our participants with greater baselineV O 2 max .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Waldron et al. (2019) investigated the time course changes in V̇O2max in temperate environment during and up to 10 days post‐HA and showed that V̇O2max was significantly different only at 4 days post‐HA (or 96 h after the last session). In short, it is still unclear if HA independently improves aerobic fitness in temperate environments, and outcomes are likely dictated by the HA protocol, time course changes and population studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another meta-analysis has extensively examined the timeline of HA decay and concluded that internal body temperature and heart rate responses typically decay at a rate of 2.5% per day (Daanen et al, 2018). The importance of recovery has even been examined and reported when seeking optimal training improvements in a thermoneutral environment and 96 h of rest following training was suggested (Waldron et al, 2019). The results from both of these manuscripts point to the importance of finding the appropriate balance between recovery and acclimation decay for optimal performance results.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to acclimation, as a control trial, two HST’s (HST1 vs. HST2) were performed and separated by 1 week. The post acclimation HST3 was performed within a week (5 ± 2 days) of the final acclimation day to prevent the decay of acclimation (Garrett et al, 2009) and we acknowledge there may be some variability in the magnitude of response (Waldron et al, 2019). To control for menstrual cycle phase the HST2 (Pre-) and HST3 (Post-) STHA trials were performed in week three of the menstrual cycle (luteal phase), in the active pill portion of the OCP for all participants.…”
Section: Methodsmentioning
confidence: 99%